2016
DOI: 10.1016/j.tcs.2016.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Proper orientation of cacti

Abstract: International audienceAn orientation of a graph G is proper if two adjacent vertices have different in-degrees. The proper-orientation number − → χ (G) of a graph G is the minimum maximum in-degree of a proper orientation of G. In [1], the authors ask whether the proper orientation number of a planar graph is bounded. We prove that every cactus admits a proper orientation with maximum in-degree at most 7. We also prove that the bound 7 is tight by showing a cactus having no proper orientation with maximum in-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 6 publications
0
31
0
1
Order By: Relevance
“…In what follows, we give an alternative and shorter proof of this theorem which results in a polynomial-time algorithm. We start by recalling a result of [3] about proper orientation of paths.…”
Section: Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…In what follows, we give an alternative and shorter proof of this theorem which results in a polynomial-time algorithm. We start by recalling a result of [3] about proper orientation of paths.…”
Section: Treesmentioning
confidence: 99%
“…Lately, Araujo et al [3] proved that the problem of determining the proper orientation number of a graph remains NP-hard for subclasses of planar graphs that are also bipartite and of bounded degree. In the same paper, they proved that the proper orientation number of any tree is at most 4.…”
Section: Introductionmentioning
confidence: 99%
“…The proper orientation number of G, denoted by − → χ (G), is the minimum integer k such that G admits a proper k-orientation. Proper orientation number is defined by Ahadi and Dehghan [1], and see the related research [2,3,6]. Knox et al [6] showed the following.…”
Section: Introductionmentioning
confidence: 99%
“…In the same paper, they proved that the proper orientation number of any tree is at most 4; Knox et al [16] provided a shorter proof of the same result. In another paper, Araújo et al [5] proved that the proper orientation number of cacti is at most 7, and that this bound is tight.…”
Section: Introductionmentioning
confidence: 99%